An improved solvent extraction method for the analysis of catechins and caffeine in green tea - Sathira Hirun (2018)
The aims of this research were to improve the stability of green tea catechins (GTC) in order to make the HPLC analysis more accurate. Five solutions were selected to study the efficiency of GTC extraction: hot water (90 °C), roomtemperature water (22 °C), methanol, ethanol and 75% ethanol. The study showed that the most efficient solvent for extraction of GTC was methanol followed by 75% (v/v) ethanol, hot water, room-temperature water and ethanol. In addition, it was found that (-)-epigallocatechin-3-gallate (EGCG) was unstable in hot water infusion as the EGCG content sharply decreased after 30 min at room temperature. In contrast, caffeine and other GTC were more stable in hot water infusion and their contents did not significantly change until the end of the experiment (90 min). However, the study revealed that when the hot water infusion was cooled on ice, the quantity of GTC was 10% higher than for methanol, and when the pH was adjusted to below 4 after cooling, the quantity of GTC was 20% higher than for methanol. In conclusion, placing the infusions on ice and adjusting the pH to below 4 dramatically improved the HPLC analysis of GTC and caffeine in green tea. © 2011 VÚP Food Research Institute, Bratislava.